2014
DOI: 10.5751/es-06523-190264
|View full text |Cite
|
Sign up to set email alerts
|

From theoretical to actual ecosystem services: mapping beneficiaries and spatial flows in ecosystem service assessments

Abstract: ABSTRACT. Ecosystem services mapping and modeling has focused more on supply than demand, until recently. Whereas the potential provision of economic benefits from ecosystems to people is often quantified through ecological production functions, the use of and demand for ecosystem services has received less attention, as have the spatial flows of services from ecosystems to people. However, new modeling approaches that map and quantify service-specific sources (ecosystem capacity to provide a service), sinks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
126
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(140 citation statements)
references
References 46 publications
1
126
0
4
Order By: Relevance
“…The literature about mapping of ESs (see, e.g., [30][31][32][33]) suggested that an effective operationalization of ES flows is difficult to achieve. This is because commonly, no distinction is made between the flow of the service and the action required by the beneficiary to benefit from the service.…”
Section: Scale (Mis)matches: Supply-demand Areas and The Planning Regmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature about mapping of ESs (see, e.g., [30][31][32][33]) suggested that an effective operationalization of ES flows is difficult to achieve. This is because commonly, no distinction is made between the flow of the service and the action required by the beneficiary to benefit from the service.…”
Section: Scale (Mis)matches: Supply-demand Areas and The Planning Regmentioning
confidence: 99%
“…In the latter, pollination can be defined as an intermediate service, while the production of fresh fruit is a final service. If the focus is on landscape livability, it is important to work on final services and not on intermediate ones, as the selection of final services makes possible the quantification and spatial identification of the service users [33,39] that are located in the URs and comprise a key element to quantify livability.…”
Section: Scale (Mis)matches: Supply-demand Areas and The Planning Regmentioning
confidence: 99%
“…To date, much more work has addressed ecological dimensions than social dimensions (Bagstad et al 2014), yet both need more balanced treatment (Spangenberg et al 2014, Bennett et al 2015.…”
Section: Advantages Of Multifaceted Ecosystem Services Analysismentioning
confidence: 99%
“…Furthermore, acknowledging the necessity of taking into account social components, some have integrated demand into trade-off assessments for a single ES, e.g., pollination (Schulp et al 2014), or for multiple ES (García-Nieto et al 2013, Hauck et al 2013, Palomo et al 2013. Finally, ES use of facets has been considered to characterize the (mis)matches between supply and demand (Bagstad et al 2014, Van der Biest et al 2014). However, although ES facets are part of the many criteria proposed to characterize and classify trade-offs and synergies between ES (Mouchet et al 2014, Van der Biest et al 2014), most assessments have been carried out irrespective of the distinction between ES facets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation